The Discovery of Grounded Theory Practices for Software Engineering Research - Razali, Rozilawati; Alqudah, Mashal Kasem; Zainal, Dzulaiha Aryanee Putri (Electronic journal of business research methods, 2021)
Software engineering (SE) research addresses not only technical issues but also human behaviour. SE is considered as an immature discipline because many technical and social issues concerning software development and management have yet to be specified. SE in general is inclined towards quantitative approaches. Nevertheless, qualitative methods are still appropriate for SE research as the methods encourage deep understanding of subject matter. Grounded Theory (GT) is regarded as one of the potential qualitative methods that is applicable to SE research. The method is able to transform less and unknown SE phenomena into cohesive theories through systematic discovery of empirical data from the ground. This paper shares some encounters of using GT in SE research based on the reflection made on several SE research projects covering various phases of software development life cycle. The encounters are then transformed into adaptations and classified as GT practices for SE research, as an effort to inspire the spirit of using GT in SE particularly among novices. The practices embrace aspects concerning formulating research questions, handling preconceptions, utilising software tools, getting access to data and presenting theory and its development process. To illustrate on how the practices were derived, a case study is presented. The proposed GT practices could act as the starting point of adopting GT in SE research. They shall be refined and improved in future to possibly become best practices when more and more experience of using GT in SE are obtained.